Root Diseases Ganoderma sp. on the Sengon in West Java and East Java - Elis Nina Herliyana; Darmono Taniwiryono; Hayati Minarsih (Jurnal Manajemen Hutan Tropika, 2012)
Sengon tree (Paraserianthes falcataria (L.) Nielsen) currently becomes a major forest tree species widely planted by smallholders in Indonesia. The wood of this is quick growing and relatively easy to sell. However, level of plant safety sengon between crop plantations and other forestry need to be assessed considering the sengon tree is alternative host of Ganoderma spp. Studies have been conducted to know the presence and diversity of Ganoderma spp. on the sengon tree and some ways inoculation on sengon plant in the nursery. Survey of Ganoderma conducted in several locations of community forests and cacao (Theobroma cacao) plantations in West Java and East Java. Testing of genetic diversity based on RAPD technique. This conducted at the Biotechnology Research Institute of Plantation Indonesia Bogor. Inoculation testing conducted at the Faculty of Forestry, Bogor Agricultural University. The results showed that Ganoderma lucidum was found on the sengon tree and cacao plant, generally on the dead stump. The test results of genetic diversity obtained genetic similarity between G. lucidum from sengon and cacao are quite close. The results of inoculation of G. lucidum testing on seedlings sengon showed that both isolate from cacao and sengon tree able to infect a sengon tree back. The existence of sengon tree as shade plants for cacao plant need to watch out, because production cycle of sengon tree faster than production cycle of cacao plant that is protected.